Large-Scale Agricultural Management and Soil Meso- and Macrofauna Conservation in the Argentine Pampas - Bedano, José Camilo (2016)
Soil is the most basic resource for sustainable agricultural production; it promotes water quality, is a key component of the biogeochemical cycles and hosts a huge diversity of organisms. However, we are not paying enough attention to soil degradation produced by land use. Modern agriculture has been successful in increasing yields but has also caused extensive environmental damage, particularly soil degradation. In the Argentine Pampas, agriculturization reached a peak with the generalized use of the no-till technological package: genetically modified soybeans tolerant to glyphosate, no-till, glyphosate, and inorganic fertilizers. This phenomenon has been widely spread in the country; the no-till package has been applied in large areas and has been used by tenants in a 60%-70% of cultivated lands. Thus, those who were involved in developing management practices may not be the same as those who will face degradation issues related to those practices. Indeed, most evidence reviewed in this paper suggests that the most widely distributed practices in the Pampas region are actually producing severe soil degradation. Biological degradation is particularly important because soil biota is involved in numerous soil processes on which soil functioning relies, affecting soil fertility and productivity. For example, soil meso- and macrofauna are especially important in nutrient cycling and in soil structure formation and maintenance, and they are key components of the network that links microbial process to the scale of fields and landscapes where ecosystem services are produced. However, the knowledge of the impact of different agricultural managements on soil meso- and macrofauna in Pampas agroecosystems is far from conclusive at this stage. The reason for this lack of definite conclusions is that this area has been given less attention than in other parts of the world; the response of soil fauna to agricultural practices is complex and taxa-dependent; and there is a wide variety of practices in the main types of agricultural systems, making generalizations difficult. A review of the existing studies on soil meso- and macrofauna in agroecosystems, revealed that (a) agricultural soils, regardless of farming system, are strongly modified in biological aspects compared to the same soils without human interventions; (b) there are no conclusive results about no-till benefits compared to reduced tillage or conventional tillage; (c) agricultural managements that are alternative to the traditional conventional systems are very poorly represented in research.